Controlling inflation with switching monetary and fiscal policies: expectations, fiscal guidance and timid regime changes - Guido Ascari; Anna Florio; Alessandro Gobbi (Bank of Finland, 2017)
Inflation depends on both monetary and fiscal policies and on how agents believe that these policies will evolve in the future. Can monetary policy control inflation, when both monetary and fiscal policies are allowed to change over time? To analyse this problem, we study a model in which both monetary and fiscal policies may switch according to a Markov process. Controlling inflation entails a unique and Ricardian solution. We propose a natural generalisation of the original Leeper (1991) taxonomy, introducing the concepts of globally active (or passive) and globally switching policies to define the conditions that allow monetary policy to control inflation under Markov switching. First, monetary and fiscal policies need to be globally balanced to guarantee a unique equilibrium: globally active monetary policies need to be coupled with globally passive fiscal policies, and switching monetary policies with switching fiscal policies. Second, this distinction characterises the nature of the solutions: a globally AM/PF regime is Ricardian, while a globally switching regime features expectation and wealth effects. Third, the strength of policy deviations across regimes is key, insofar a globally active (or passive) policy allows only timid deviations. Finally, our framework can rationalise the impulse responses from a Bayesian VAR on U.S. data for the recent zero lower bound period as being due to "timidity" in fiscal actions that have been unable to spur inflation.
URN:NBN:fi:bof-201705051266
Keywords: E58; E63; 330